Β6‐integrin serves as a novel serum tumor marker for colorectal carcinoma. Issue 3 (29th January 2019) - Bengs, Susan; Becker, Eugenia; Busenhart, Philipp; Spalinger, Marianne R.; Raselli, Tina; Kasper, Stephanie; Lang, Silvia; Atrott, Kirstin; Mamie, Celine; Vavricka, Stephan R.; von Boehmer, Lotta; Knuth, Alexander; et al.
Abstract : Colorectal cancer (CRC) is one of the leading causes of cancer‐related deaths worldwide and the need for novel biomarkers and therapeutic strategies to improve diagnosis and surveillance is obvious. This study aims to identify β6 ‐integrin (ITGB6) as a novel serum tumor marker for diagnosis, prognosis, and surveillance of CRC. ITGB6 serum levels were validated in retro‐ and prospective CRC patient cohorts. ITGB6 serum levels were analyzed by ELISA. Using an initial cohort of 60 CRC patients, we found that ITGB6 is present in the serum of CRC, but not in non‐CRC control patients. A cut‐off of ≥2 ng/mL ITGB6 reveals 100% specificity for the presence of metastatic CRC. In an enlarged study cohort of 269 CRC patients, ITGB6 predicted the onset of metastatic disease and was associated with poor prognosis. Those data were confirmed in an independent, prospective cohort consisting of 40 CRC patients. To investigate whether ITGB6 can also be used for tumor surveillance, serum ITGB6‐levels were assessed in 26 CRC patients, pre‐ and post‐surgery, as well as during follow‐up visits. After complete tumor resection, ITGB6 serum levels declined completely. During follow‐up, a new rise in ITGB6 serum levels indicated tumor recurrence or the onset of new metastasis as confirmed by CT scan. ITGB6 was more accurate for prognosis of advanced CRC and for tumor surveillance as the established marker carcinoembryonic antigen (CEA). Our findings identify ITGB6 as a novel serum marker for diagnosis, prognosis, and surveillance of advanced CRC. This might essentially contribute to an optimized patient care. Abstract : What's new? While serum biomarkers are ideal tools for colorectal cancer (CRC) detection, the identification of a marker with both high sensitivity and high specificity has proven challenging. Here, the authors investigated β6 ‐integrin (ITGB6), a molecule upregulated in association with epithelial‐to‐mesenchymal transition activities, such as wound healing and carcinogenesis, for its biomarker potential in CRC. In patients, ITGB6 serum levels were significantly associated with CRC diagnosis and prognosis. A cut‐off of ≥2 ng/mL ITGB6 reliably predicted metastatic disease and poor CRC prognosis. The findings suggest that employing ITGB6 as a serum biomarker could greatly aid diagnosis and tumor surveillance in CRC patients.